View of the Chaunsath Yogini Temple - Temples of India Project Team (Jio Institute, 2024)
Chaunsath Yogini Temple is situated amidst the Shiva Temple and Jain Temple. Located on a high plinth, the temple has evidently been significantly damaged because of which its mandapa has not survived. The architectural patterns of the temple are different from most other temples in the Arthuna group.